Are women always better able to recognize faces? The unveiling role of exposure time - Torben Hansen (Public Library of Science (PLoS), 2021)
A longer exposure time generally improves individuals’ ability to recognize faces. The current research investigates whether this effect varies between genders and whether it is influenced by the gender of the exposed faces. Based on a set of four experimental studies, we advance our knowledge of face recognition, gender, gender distribution of exposed faces, and exposure time in three main ways. First, the results reveal that women are more likely than men to suffer from a decrease in face recognition ability due to a lower exposure time. Second, the findings show that when exposure time is short (vs. long) women recognize a larger proportion of same gender faces and also recognize a larger proportion of same gender faces as compared with the proportion of same gender faces recognized by men. Third, findings reveal that when individuals are only exposed to same gender faces, women recognize more faces than men regardless whether exposure time is short, or long. In short, the findings of this research suggest that insight into the interplay between gender and exposure time length is critical to appropriately determine human beings’ ability to recognize faces.